Moj pervyj medved - Petro Milimov; Andrey Filchenko; Olga Potanina; Julia Kurganskaja; Maria Tonoyan; Sergej Kovylin (Andrey Filchenko, 2012)
Eastern Khanty Comprehensive Documentation & Analysis of two Endangered Siberian Languages: legacy data and last speakers of Eastern Khanty and Southern Selkup Biographical story